IMRC-exo alleviates limb injury by inhibiting ferroptosis in a rabbit model of deinagkistrodon acutus snakebite envenomation - Linjie Lai; Wang Du; Haohao Wu; Wanjuan Liu; Ke lv; Peixin Shangguan; Lutao Xie; Jiefeng Xu; Pin Lan (Scientific Reports)
Abstract Deinagkistrodon acutus is one of the unique venomous snakes native to Southeast Asia. Limb injury caused by this species is the main cause of disability in snake bite patients, while the relevant pathogenesis mechanism and intervention strategies need to be further explored. In recent years, studies have established that mesenchymal stem cell-derived exosome (MSC-Exo) exerts a positive therapeutic effect on reducing limb injuries caused by a variety of factors, but this effect in limb injuries caused by snake bite is still unclear. Immunity-and-matrix regulatory cell (IMRC) is a type of mesenchymal stem cell derived from human embryonic stem cells, characterized by its unique capabilities in immune regulation and regulation of extracellular matrix production. In this study, IMRC was selected to investigate the effects and mechanisms of its Exo on limb injury induced by Deinagkistrodon acutus venom. Eighteen healthy male white rabbits were divided into Sham (S) group, Snake venom (SV) group and SV + IMRC-Exo group according to a random number table, with 6 rabbits in each group. Rabbit models of snakebite were established by limb injection of 1.5 mg/kg snake venom, followed by intravenous injection of 80 U/kg antivenom 2 h later. Additionally, subcutaneous injection of 7.5 × 1010 particles of Exo in the SV + IMRC-Exo group was given. After modeling, the limb circumference was measured regularly and the serum levels of muscle injury markers such as Creatine Kinase (CK) and Myoglobin (Mb) were detected. At the end of the experiment, muscle tissue samples of the injured limb were obtained to detect gross pathological damage and cell apoptosis. Ferroptosis-related products including iron deposition, reactive oxygen species(ROS), malondialdehyde (MDA), 4-hydroxynonenal (4-HNE), glutathione (GSH), and superoxide dismutase (SOD)were quantified, and key proteins including acyl-CoA synthetase long chain family member 4 gene (ACSL4), nicotinamide adenine dinucleotide phosphate oxidase 1 (NOX1), cyclooxygenase-2 (COX2), glutathione peroxidase 4 (GPX4), and ferritin heavy chain 1 (FTH1) were measured. Compared with group S, the limb circumference and CK and Mb levels were significantly increased after modeling in the SV group and the SV + IMRC-Exo groups. However, the limb circumference and levels of muscle injury markers were significantly lower in the SV + IMRC-Exo group than in the SV group. Histopathological analysis showed that those animals in the SV and SV + IMRC-Exo groups had obvious muscle tissue damage and apoptosis compared with the S group. However, these pathological changes were significantly milder in the SV + IMRC-Exo group than in the SV group. In addition, compared with group S, the levels of iron deposition, ROS, MDA and 4-HNE, and the mRNA expression of ACSL4, NOX1 and COX2 in muscle tissues in the SV and SV + IMRC-Exo groups were significantly increased while the levels of GSH and SOD, and the mRNA expression of GPX4 and FTH1 were significantly decreased. However, compared with the SV group, the application of IMRC-Exo significantly reversed the changes in ferroptosis-related indices mentioned above. IMRC-Exo has a protective effect on limb injury induced by Deinagkistrodon acutus venom in rabbits, in which the mechanism is potentially related to the inhibition of ferroptosis.